STRATEGI ALIANSI PERUSAHAAN JASA PENGIRIMAN DALAM MENINGKATKAN KEUNGGULAN BERSAING GLOBAL (STUDI PADA PT. HIJAU ABADI) - Farizki, Abdul Ro’uf (Arthavidya Jurnal Ilmiah Ekonomi, 2021)
Abstract :Today, companies are demanded to always develop and continuesly changes. Organizational development is one of the management systems to improve, develop, and change the company's internal operations. In the era industrial 4.0, companies are required to continue to make changes, if not, it will incur a fatal effect on the company's operational structure and impact on performance degradation. One type of organizational development that is currently rife is alliancesstrategic. The alliance strategy canapplied with companies that have the same vision & mission and need to sharing capabilities & core competences. This is what is implemented by Hijau Abadi, implementing a global alliance strategy with shipping service companies that have 58 years of experience in the industry. This research is a descriptive study with a qualitative approach. Data collection techniques used by researchers are observing and in depth interview methods. This study aims to obtain information on the impact of Hijau Abadi implementing the alliance strategy and how the company can improve competitive advantage of this collaboration, and whether the alliance collaboration implemented with right partner, and whether the alliance collaboration implemented has been successfully applied by Hijau Abadi. Key word: organizational development, alliance strategy, competitive advantage, shipping line service.